KÓRKEM ShÍǴARMALARDA DIALEKTLIK VARIANTLARDÍŃ QOLLANÍLIWÍ - Xalmuratova, D.Y. (SCIENCE and SOCIETY, 2025)
This article deals with dialectal variants found in the language of artistic works, the variants of individual words, and the variants of words in phraseology.